Application of thyroglobulin detection in fine-needle aspiration washout fluid from cervical lymph node - ZENG Qingxin, ZHONG Haifeng (Xin yixue)
Differentiated thyroid carcinoma （DTC） is the most common type of thyroid malignancy， with a high incidence of regional lymph node metastasis. Accurate diagnosis of lymph node metastasis is crucial for determining appropriate treatment strategies. Fine-needle aspiration （FNA） is an important method for evaluating the nature of thyroid nodules and lymph node metastasis. In recent years， the detection of thyroglobulin （Tg） levels in FNA washout fluid has received widespread attention as a supplementary tool for cytological examination. FNA-Tg can increase the detection rate of cytology- negative lymph node metastasis， with high sensitivity and specificity. Combined with other diagnostic methods such as serology examination and imaging analysis， it can further enhance diagnostic value. However， there is currently a lack of standardized procedures for FNA-Tg operation and specimen handling. The methodological and interpretative standards for quantitative Tg have not been established. And it is still controversial whether various factors， such as thyroid hormone replacement therapy， Tg autoantibodies， and residual thyroid tissue， affect the results of FNA-Tg. This article reviews the current status and dilemma of the application of FNA-Tg testing in neck lymph nodes to provide a reference for the clinical application of FNA-Tg testing in the diagnosis of lymph node metastasis in DTC.